Fluorescent membrane probes based on a coumarin-thiazole scaffold - Pajk, Stane (Acta chimica slovenica, 2019)
Biological functions of cell membranes and their correlation to the heterogeneity of the latter%s lipid composition are still poorly understood. Fluorescence provides one of the most versatile tools for studying biological membranes. However, few bright and photostable fluorescent probes for labeling plasma membranes are available. We have designed and synthesized two such probes, 8 and 9, that are based on the thiazole-coumarin scaffold. Both are environment sensitive and exhibit similar shifts of emission spectra in a variety of solvents as probes based on 7-nitrobenz-2-oxa-1,3-diazol-4-yl (NBD). In particular, the second, positively charged probe 9 labels the plasma membrane selectively with limited redistribution to other membranes of the cell. Unfortunately, compared to the other two probes tested, 8 and 6-NBD-PC, it exhibits the highest rate of photobleaching. Nevertheless, these new thiazole-coumarin based membrane probes provide a viable approach to the design of novel membrane probes.